2015
DOI: 10.1371/journal.pone.0119761
|View full text |Cite
|
Sign up to set email alerts
|

TatBC-Independent TatA/Tat Substrate Interactions Contribute to Transport Efficiency

Abstract: The Tat system can transport folded, signal peptide-containing proteins (Tat substrates) across energized membranes of prokaryotes and plant plastids. A twin-arginine motif in the signal peptide of Tat substrates is recognized by TatC-containing complexes, and TatA permits the membrane passage. Often, as in the model Tat systems of Escherichia coli and plant plastids, a third component – TatB – is involved that resembles TatA but has a higher affinity to TatC. It is not known why most TatA dissociates from Tat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 82 publications
2
23
0
Order By: Relevance
“…In that study, also MD simulations were carried out that indicated intensive contacts between the APH of TatA and mainly the c-domain of the signal peptide. This fully agrees with the fact that the RR-motif is not recognized by TatA (26). MD simulations of TatA in membranes suggest that only oligomeric TatA assemblies can destabilize the membrane (6).…”
Section: Substrate-inducedsupporting
confidence: 79%
See 4 more Smart Citations
“…In that study, also MD simulations were carried out that indicated intensive contacts between the APH of TatA and mainly the c-domain of the signal peptide. This fully agrees with the fact that the RR-motif is not recognized by TatA (26). MD simulations of TatA in membranes suggest that only oligomeric TatA assemblies can destabilize the membrane (6).…”
Section: Substrate-inducedsupporting
confidence: 79%
“…We have recently demonstrated that TatA can interact with Tat substrates in a signal peptide-dependent, RRindependent manner (26). In that study, also MD simulations were carried out that indicated intensive contacts between the APH of TatA and mainly the c-domain of the signal peptide.…”
Section: Substrate-inducedmentioning
confidence: 92%
See 3 more Smart Citations